SISTEM MANAJEMEN INFORMASI BIAYA: SINERGI EVALUASI KARAKTERISTIK BIAYA DENGAN TEKNOLOGI DIGITAL - Irvan satria haloho; Cindy Riski Silalahi; Abel Theresia siregar; Pitta Cristina Hutasoit; Kristina manik; Hamonangan Siallagan (Universitas Negeri Medan, 2025)
The era of digital transformation has changed the paradigm of information management in various organizational sectors, especially in cost management, which is an important element in strategic decision making. Rapid developments in information technology have encouraged organizations to optimize their cost management systems through the integration of more sophisticated digital technologies. This study examines the application of a digital-based cost information management system (SMIB) in an organization that is undergoing a comprehensive digital transformation. This case highlights a unique phenomenon related to changes in cost characteristics that cannot be predicted by conventional systems. The findings show that the synergy between cost characteristic evaluation and digital technology offers innovative solutions to existing challenges. The integration of technologies such as big data analytics and machine learning improves the accuracy and speed of cost data processing, providing deeper insights for strategic decision-making. This study concludes that the development of adaptive cost information management systems is increasingly relevant given the operational complexity of modern organizations. The implementation of an integrated CMIS can result in significant efficiency improvements, as evidenced by an increase in operational efficiency of up to 35% compared to conventional systems.